2011
DOI: 10.1158/1535-7163.mct-11-0312
|View full text |Cite
|
Sign up to set email alerts
|

Targeting FGFR/PDGFR/VEGFR Impairs Tumor Growth, Angiogenesis, and Metastasis by Effects on Tumor Cells, Endothelial Cells, and Pericytes in Pancreatic Cancer

Abstract: Activation of receptor tyrosine kinases, such as fibroblast growth factor receptor (FGFR

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
86
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(93 citation statements)
references
References 47 publications
(67 reference statements)
3
86
0
1
Order By: Relevance
“…Further in vivo and in vitro data indicate that this drug blocked PDGFR/FGFR/VEGFR signaling in advanced melanoma, 4 pancreatic cancer, 14 breast carcinoma, 15 urothelial carcinoma, 16 impaired tumor growth, angiogenesis, and metastasis by effects on tumor cells, endothelial cells, and pericytes in vitro. 14,15 Due to the important role of PDGFs and FGFs in the supportive effect of CAFs for the breast tumor progression through the autocrine or paracrine fashion, [17][18][19] we hypothesized that targeting PDGFR and FGFR signaling by Dovitinib could block the cross-talk of CAFs-tumor cell and inhibit cell invasion of breast cancer. We selected an in vitro transwell chamber model for co-culture of breast cancer cells with CAFs and investigation of breast cancer cell invasion in this study.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Further in vivo and in vitro data indicate that this drug blocked PDGFR/FGFR/VEGFR signaling in advanced melanoma, 4 pancreatic cancer, 14 breast carcinoma, 15 urothelial carcinoma, 16 impaired tumor growth, angiogenesis, and metastasis by effects on tumor cells, endothelial cells, and pericytes in vitro. 14,15 Due to the important role of PDGFs and FGFs in the supportive effect of CAFs for the breast tumor progression through the autocrine or paracrine fashion, [17][18][19] we hypothesized that targeting PDGFR and FGFR signaling by Dovitinib could block the cross-talk of CAFs-tumor cell and inhibit cell invasion of breast cancer. We selected an in vitro transwell chamber model for co-culture of breast cancer cells with CAFs and investigation of breast cancer cell invasion in this study.…”
Section: Introductionmentioning
confidence: 97%
“…9 Among these cytokines, CCL2 and CCL5, which are known inflammatory mediators, were demonstrated to play important role in the mediation of the interaction between CAFs and breast cancer cells beyond SDF-1 [10][11][12][13] Dovitinib (formerly CHIR-258, TKI-258, Novartis pharmaceuticals) is an investigational new inhibitor of multiple tyrosine kinases that has in vitro inhibitory activity against basic fibroblast growth factor receptor (bFGFR), platelet-derived growth factor receptor (PDGFR), and vascular endothelial growth factor receptor (VEGFR) kinases with IC 50 values of approximately 10 nM. Further in vivo and in vitro data indicate that this drug blocked PDGFR/FGFR/VEGFR signaling in advanced melanoma, 4 pancreatic cancer, 14 breast carcinoma, 15 urothelial carcinoma, 16 impaired tumor growth, angiogenesis, and metastasis by effects on tumor cells, endothelial cells, and pericytes in vitro. 14,15 Due to the important role of PDGFs and FGFs in the supportive effect of CAFs for the breast tumor progression through the autocrine or paracrine fashion, [17][18][19] we hypothesized that targeting PDGFR and FGFR signaling by Dovitinib could block the cross-talk of CAFs-tumor cell and inhibit cell invasion of breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…17), that has shown antitumor and antiangiogenic effects in preclinical models of colon, breast, bladder, pancreatic, and renal cell cancers (18)(19)(20)(21)(22)(23). Here, we show antitumor activity in preclinical models of RCC and report on the dose escalation portion of a phase I/II study (NCT00715182) to identify the maximum tolerated dose (MTD) of dovitinib on a 5-days-on/2-days-off dosing schedule in repeating 28-day cycles (starting dose, 500 mg) in patients with advanced RCC or mRCC refractory to standard therapies.…”
Section: Introductionmentioning
confidence: 99%
“…Blocking FGFR1 and FGFR2 reduces the levels of VEGF and neovascularization [183]. A study reported an increase in the levels of VEGF and VEGFR1/2 along with the levels of an angiogenic factor Hif-1α, observed in epithelial cells of the prostate tumor, upon induction of FGFR1 [184,185]. FGFR1 functions to promote the paracrine signaling of VEGF on endothelial cells to execute angiogenesis.…”
Section: Fgfs and Fgfrs: Roles In Angiogenesismentioning
confidence: 99%